Application of NAA to air particulate matter collected at thirteen sampling sites in eight Asian countries: A collaborative study - M., Ebihara; Y. S., Chung; H. M., Dung; J. H., Moon; B.-F., Ni; T., Otoshi; Y., Oura; F. L., Santos; F., Sasajima; Sutisna, -; B. S., Wee; W., Wimolwattanapun; et al. (Akadémiai Kiadó, Budapest, 2008)
Air particulate matter (APM) samples (PM2.5 and PM10–2.5) were collected at 13 sampling points in 8 Asian countries and their chemical compositions were determined by using neutron activation analysis (NAA) with the k0-standardization method in addition to conventional comparative method of NAA. Analytical data showed that mass concentration and elemental composition of the APM collected are variable in terms of time and space, and are related to the characteristics of the sampling sites concerned. NAA was proved to be highly effective for the regional characterization of APM in chemical composition.